The Role of Morpheme Resources of the Russian Language in the Creation of Neologisms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Implementation of the potential capabilities of the Russian word‑formation system is impossible without the use of morphemic resources and word‑formation methods inherent in the Russian language. The modern state of Russian is characterized by extremely active borrowing processes of extensive layers of vocabulary related to various spheres of life: economics, politics, sports, art, etc. Sometimes entire lexical series with uniform structure are borrowed (for example: hamburger, cheeseburger, kopburger; yogurt, frugurt, apigurt, emigurt; clipmaker, imagemaker, newsmaker, hitmaker, playmaker). This abundance of borrowed words inevitably leads to a qualitative shift: certain structural elements begin to stand out within these series, developing more or less concrete meanings. Thus, foreign structural elements begin to form as independent morphemes in Russian—i.e., the process of morphemization occurs.